Branched-Chain Amino Acids Have Equivalent Effects to Other Essential Amino Acids on Lifespan and Aging-Related Traits in Drosophila. (20th March 2019) - Juricic, Paula; Grönke, Sebastian; Partridge, Linda
Abstract: Branched-chain amino acids (BCAAs) have been suggested to be particularly potent activators of Target of Rapamycin (TOR) signaling. Moreover, increased circulating BCAAs are associated with higher risk of insulin resistance and diabetes in both mice and humans, and with increased mortality in mice. However, it remains unknown if BCAAs play a more prominent role in longevity than do other essential amino acids (EAAs). To test for a more prominent role of BCAAs in lifespan and related traits in Drosophila, we restricted either BCAAs or a control group of three other EAAs, threonine, histidine and lysine (THK). BCAA restriction induced compensatory feeding, lipid accumulation, stress resistance and amelioration of age-related gut pathology. It also extended lifespan in a dietary-nitrogen-dependent manner. Importantly, the control restriction of THK had similar effects on these phenotypes. Our control diet was designed to have every EAA equally limiting for growth and reproduction, and our findings therefore suggest that the level of the most limiting EAAs in the diet, rather than the specific EAAs that are limiting, determines the response of these phenotypes to EAA restriction.